REVIEW OF EMPIRICAL RESEARCH ON SPORTS EDUCATIOIN MODEL (SEM) IN RECENT FIVE YEARS (2019 - PRESENT) - Xiaoyuan Liu,; Radzliyana Binti Radzuwan,; Nadiah Diyana Tan Binti Abdullah, (Journal of Islamic, Social, Economics and Development, 2024)
Siedentop developed SEM to provide students with sports knowledge. As more and more researchers continue to study SEM, empirical research has become the content of most researchers' research on SEM. By using the method of literature review, the researcher obtained and sorted out relevant literature through google research, WOS, CNKI and other databases, in order to provide evidence to support the view that this model can realize physical education learning. The research aim to summarize and analyze the empirical research conclusions of SEM in recent five years, and provide some valuable reference for the application and development of SEM in physical education in China. This study is the latest review of SEM empirical research, including the latest research trends in future research.